1999
DOI: 10.1111/j.1744-7348.1999.tb00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of potato cultivars in response to application of phosphate fertiliser

Abstract: Three experiments examined the response of potato cultivars from different maturity groups to fertiliser phosphorus application under conditions of relatively low residual soil P. Initial expansion of the leaf canopy was much more rapid following P application and maximum cover was attained sooner. In the absence of applied P, maximum ground cover was reduced substantially in early-maturing cultivars but not in maincrop cultivars. At early harvests, all cultivars showed very large growth responses to P applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 13 publications
6
23
0
1
Order By: Relevance
“…(N deficiency: Hall et al, 1995;Salvagiotti and Miralles, 2008;Massignam et al, 2009;P deficiency: Pellerin et al, 2000;Colomb et al, 2000;Plénet et al, 2000;Fletcher et al, 2008a;Rodríguez et al, 1998aRodríguez et al, , 2000Lázaro et al, 2010;Sandaña and Pinochet, 2011;Sandaña et al, 2012). However, for potato crops there is much less information about the effects of soil constraints, particularly P deficiency, on RI and its impact on total biomass and tuber yield (Harris, 1992;Jenkins and Ali, 1999). Jenkins and Ali (1999), in three experiments using different cultivars (up to 5) and P rates (0-400 kg P 2 O 5 ha −1 ), concluded that P deficiency decreased dry matter production through reductions in RI.…”
Section: Introductionmentioning
confidence: 95%
“…(N deficiency: Hall et al, 1995;Salvagiotti and Miralles, 2008;Massignam et al, 2009;P deficiency: Pellerin et al, 2000;Colomb et al, 2000;Plénet et al, 2000;Fletcher et al, 2008a;Rodríguez et al, 1998aRodríguez et al, , 2000Lázaro et al, 2010;Sandaña and Pinochet, 2011;Sandaña et al, 2012). However, for potato crops there is much less information about the effects of soil constraints, particularly P deficiency, on RI and its impact on total biomass and tuber yield (Harris, 1992;Jenkins and Ali, 1999). Jenkins and Ali (1999), in three experiments using different cultivars (up to 5) and P rates (0-400 kg P 2 O 5 ha −1 ), concluded that P deficiency decreased dry matter production through reductions in RI.…”
Section: Introductionmentioning
confidence: 95%
“…Phosphorus is an essential plant nutrient that is especially important in promoting early crop growth (Jenkins and Ali 1999). Potatoes are responsive to P fertilization on soils testing low in P, but yield increases from applied P have also been found on soils testing very high in P (Sanderson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the TB of potato cultivars due to P fertilization had also been reported by Dyson and Watson (1971) and Jenkins and Ali (1999). On the other hand, a reduction in the TB or growth rate under P deficient conditions had also previously been described (Dechassa et al 2003: Covarrubias-Ramírez 2005Zelalem, et al 2009;Fleisher et al 2013) and attributed to a limited amount of photosynthetically active radiation being absorbed (Colomb et al 1995) and/or to a less efficient conversion of the intercepted radiation (Plénet et al 2000).…”
Section: Dry Matter Accumulationmentioning
confidence: 66%